Pulmonary embolism, part II: Management - Bĕlohlávek, Jan; Dytrych, Vladimír; Linhart, Aleš (Experimental and clinical cardiology, 2013)
Acute pulmonary embolism (PE) bears a significant burden on health and survival. Rapid and accurate risk stratification and management are of paramount importance to ensure the highest quality of care. This present article summarizes currently available and emerging management strategies for the disease. The authors not only review current evidence regarding early therapy of acute PE, including supportive care, anticoagulation, thrombolysis, surgical and catheter-based treatment, but also the possible role of mechanical circulatory support in PE. The authors also discuss complications related to PE and its management.
Keywords: Catheter-based management; Thrombolysis; Supportive care; Pulmonary embolism; Surgical embolectomy; Anticoagulation